Celastrol Attenuates Lipid Accumulation and Stemness of Clear Cell Renal Cell Carcinoma via CAV-1/LOX-1 Pathway - Zhang, Chan-Juan; Zhu, Neng; Wang, Yu-Xiang; Liu, Le-Ping; Zhao, Tan-Jun; Wu, Hong-Tao; Liao, Duan-Fang; Qin, Li (Frontiers in Pharmacology, 2021)
Clear cell renal cell carcinoma (ccRCC) is characterized by abnormal lipid accumulation. Celastrol is a pentacyclic triterpene extracted from Tripterygium wilfordii Hook F with anti-cancer activity. In the present study, the anticancer effects of celastrol on ccRCC and the underlying mechanisms were studied. Patients with reduced high density lipoprotein (HDL) and elevated levels of triglyceride (TG), total cholesterol (TC), low density lipoprotein (LDL) was found to have higher risk of ccRCC. In ccRCC clinical samples and cell lines, caveolin-1 (CAV-1) was highly expressed. CAV-1 was identified as a potential prognostic biomarker for ccRCC. Celastrol inhibited tumor growth and decreased lipid deposition promoted by high-fat diet in vivo. Celastrol reduced lipid accumulation and caveolae abundance, inhibited the binding of CAV-1 and lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) in ccRCC cells. Furthermore, celastrol attenuated stemness through blocking Wnt/β-catenin pathway after knockdown of CAV-1 and LOX-1. Therefore, the findings suggest that celastrol may be a promising active ingredient from traditional Chinese medicine for anti-cancer therapy.